Arthroscopically assisted anterior cruciate ligament reconstruction with bone-patellar tendon-bone autograft without wound drainage: short- to middle-term outcome - Dariusz Witoński; Rafał Kęska; Rafał Cyranowski; Przemysław T. Paradowski (Videosurgery and Other Miniinvasive Techniques)
Introduction : Several studies have suggested that anterior cruciate ligament reconstruction (ACLR) without wound drainage has no impact on long-term follow-up. Aim: To investigate a prospective patient series as measured by the patient-administered disease-specific questionnaire Knee injury and Osteoarthritis Outcome Score (KOOS). Material and methods : The study included 101 consecutive patients (71 men and 30 women) with a mean age of 30 years (SD 10, range: 15–62 years), who had undergone primary single incision arthroscopic bone-patellar tendon-bone autograft (BPTB) ACLR without wound drainage. All patients completed KOOS questionnaires, preoperatively and at a mean follow-up of 1.4 years (range: 0.4–3.4). Satisfactory clinical outcome (function recovery – FR) was defined as the lower threshold for the 95% CI of 18–34-year old males and corresponded to a KOOS score > 90 for Pain, 84 for Symptoms, 91 for Activities of Daily Living (ADL), 80 for Sports/Recreation, and 81 for Quality of Life (QOL). A non-satisfactory result was defined as treatment failure (TF) and corresponded to a QOL score < 44. Results: All patients achieved 90 of knee flexion on the first postoperative day and full extension 2 weeks postoperatively. A full range of motion was achieved in less than 6 weeks postoperatively. No postoperative complications were reported. Score improvement at follow-up was observed in the KOOS subscales Pain, Symptoms and ADL. Criteria for FR were fulfilled by 52% of patients for Pain, 47% for Symptoms, 62% for ADL, 34% for Sports/Recreation and 15% for QOL, whereas criteria for TF were fulfilled by 29% of patients. Conclusions : The study demonstrated that the primary ACLRs without wound drainage did not have any negative impact for patient-reported recovery.